Association of the cumulative burden of late‐life anxiety and depressive symptoms with functional impairment. (28th October 2019) - Simning, Adam; Seplaki, Christopher L.
Abstract : Objectives: This study investigates the association of the cumulative burden of anxiety‐only, depression‐only, and comorbid anxiety and depression symptoms with (a) incident self‐care or household activities impairment among those with no baseline self‐care or household activities impairment, respectively, or (b) change in status of self‐care or household activities impairment among those with baseline impairment. Methods: This study consists of participants (N = 4619) from the National Health and Aging Trends Study, a longitudinal study that examines a nationally representative sample of US adults aged 65 years and older. Outcomes included incident or change in self‐care or household activity impairment. Primary independent variables were yearly counts of screening positive for clinically significant symptoms for anxiety‐only, depression‐only, or co‐occurring anxiety and depression. Multivariable logistic regression models examined incident impairment and change in impairment status. Results: Yearly counts of anxiety‐only symptoms were associated with incident impairment in self‐care and household activities and less improvement in self‐care functioning. Yearly counts of depression‐only symptoms were associated with incident impairment in self‐care and household activities. Yearly counts of co‐occurring symptoms of anxiety and depression were associated with incident impairment in self‐care and household activities, less improvement in self‐care activities, and worsening impairment in household activities. Conclusions: This study finds that the cumulative burden of co‐occurring anxiety and depression symptoms is associated with incident impairment in functioning, persistent self‐care impairment, and deterioration in household activity impairment. These findings emphasize the importance of managing late‐life anxiety and depressive symptoms, which are treatable, frequently co‐occur, and contribute to disability.